Prehospital Predictors for Urgent Neurosurgical Intervention in the Head Trauma Patient: A 2-Year Multicenter Retrospective Study - Jakub Nożewski; Maja Kwiatkowska; Aleksandra Łosińska; Ewa Nowak; Anna Lackowska; Anna Rydzewska; Agnieszka Durma; Paweł Sokal (Emergency Medicine International)
Background. Traumatic brain injury (TBI) is the main cause of disability in the world. Prehospital diagnosis of patients requiring rapid neurosurgical intervention and the earliest possible introduction of procedures preventing secondary brain injuries (SBI) are crucial. Methodology and Study Population. The authors of this paper assumed that certain age groups with specific injuries are more likely to require urgent neurosurgical intervention compared with patients who did not require such an intervention. Out of 54,814 head CT scans, based on the inclusion criteria, 7,864 were selected for the study. Data such as sex, age, the mechanism of injury, comorbid trauma, and abnormal findings in the examination of patients qualified for urgent neurosurgical intervention were analyzed in order to find statistically significant factors through a comparison with all head trauma patients. Results. Patients qualified for urgent neurosurgical intervention were significantly older compared with the others (63 years vs. 49 years). Patients transferred from the emergency department directly to the operating room were more often admitted to the hospital due to the fall (64.1% vs. 45.1%, p=0.004). The following were observed much more commonly among the patients qualified for urgent neurosurgical intervention than in the entire study group of subjects with traumatic brain injury (TBI), e.g., calf deformity (2.2% vs. 0.1%, p=0.019) and bleeding from the mouth (4.3% vs. 0.0%, p<0.001). On the other hand, superciliary arch wounds were observed much less commonly than in the entire group (0.0% vs. 5%, p=0.221). Conclusion. Patients admitted directly to the operating neurosurgical room from emergency departments constitute a small percentage of TBI patients, and their prognosis for normal performance status upon discharge is poor. Maximum efforts should be made to distinguish these patients and to start proper treatment even during prehospital care.